Validation of the Occupational Self-Efficacy Scale in a Sample of Chinese Employees - Peng, Jiaxi; Zhang, Jiaxi; Zhou, Xinzhou; Wan, Zhengwei; Yuan, Weizhuo; Gui, Junxiao; Zhu, Xia (Frontiers in Psychology, 2021)
Occupational self-efficacy, which refers to the belief that one is competent to fulfill work-related tasks or activities, has attracted increasing attention in recent years. The six-item version of the Occupational Self-Efficacy Scale (OSS-6) is an excellent tool for evaluating occupational self-efficacy; however, there is currently no report of the reliability and validity of the OSS-6 among Chinese people. This study aimed to translate the OSS-6 into Chinese and evaluate its reliability and validity in a sample of Chinese employees. A total of 433 junior staff at several firms completed the Chinese version of the OSS-6, the General Self-Efficacy Scale, the Rosenberg Self-Esteem Scale, the Minnesota Job Satisfaction Questionnaire, the in-role performance scale, and the career calling scale. Four weeks later, 94 participants were recalled and were retested using the OSS-6. Factor analysis results supported the one-factor model of the OSS-6. Excellent internal consistency was obtained with the OSS-6. Additionally, the OSS-6 results were significantly correlated with general self-efficacy, self-esteem, job satisfaction, in-role performance, and career calling. Furthermore, occupational self-efficacy was found to partially mediate the effects of career calling on job satisfaction and in-role performance. The results of this study supported the cross-cultural consistency of the structure of the OSS-6 and showed that the Chinese version of the OSS-6 demonstrated excellent validity and reliability. Therefore, the Chinese version of the OSS-6 can be used as an assessment tool for evaluating occupational self-efficacy in future studies.